Conceptual and preliminary design of a hybrid dust filter for helicopter engines - Bojdo, N.; Filippone, A. (My University, 2017)
We present our ongoing work in the field of helicopter engine protection. Recent sand ingestion-related aircraft crash mishaps have highlighted the inadequacy of some particle separator types to remove the finest particles from the engine inlet air, which melt more readily and are potentially more hazardous to operation that the larger, erosive quartz particles that are successfully removed. Inertia-based separators such as integrated particle separators on the T700 and RTM322 military helicopter engines, or the externally-mounted vortex tube panels are unable to separate well particles below 10 microns in size, yet the former is small and compact and the latter exhibits a low pressure loss compared to the high separation efficiency barrier filter separator. In the current work we examine these competing cost functions and present a new metric trade-off designs at the concept stage. We use this metric to demonstrate why vortex tubes may be the superior technology for ISO Coarse test dust, but barrier filters succeed for a finer, more realistic test dust called AFRL 02. Finally we propose a hybrid concept that combines the benefits of two particle separator concepts to remove a greater proportion of dust than either of the two contributory devices can do alone.